Evaluasi Pemanfaatan Teknologi Radar Dalam Rangka Penguatan Pertahanan Dan Kedaulatan Wilayah Udara Indonesia - Ikha Prasetiyani; A Farid Wadjdi; Y Prihanto; A A Supriyadi; A A Lestari; Sukendra Martha; M Supriyatno; Agus Haryanto (Journal on Education, 2023)
One source of national wealth is airspace. There is a lot of potential in the airspace, including defense and commercial potential. However, the management of airspace in Indonesia is still not optimal. This can be analyzed from airspace issues related to the Indonesian FIR area on the border of the Natuna Islands. There is still overlap with the neighborhod country, Singapore, regarding the authority to control, use and regulate the Fligt Information Region (FIR) which could impact security and air defense if not resolved immediately. That's why this article presents insights through the literacy method regarding evaluating the use of radar technology to strengthen the defense and sovereignty of Indonesia's airspace. The evaluation was carried out in terms of the hazard related to the threat of jamming issues and flight incidents that occurred. Next, analyze the vulnerabilities related to the characteristics of the FIR and the distribution of radar capabilities. The last evaluation is related to capacity starting from the budget, policies, human resources to the infrastructure owned by air defense in Indonesia. So that from the elaboration of the evaluation it is hoped that it can become one of the inputs and insights to increase the usefulness of radar in order to strengthen defense and fully acquire the sovereignty of Indonesia's airspace.